2018
DOI: 10.1186/s13058-018-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal enumeration and cluster evaluation of circulating tumor cells improve prognostication for patients with newly diagnosed metastatic breast cancer in a prospective observational trial

Abstract: BackgroundCirculating tumor cells (CTCs) carry independent prognostic information in patients with metastatic breast cancer (MBC) on different lines of therapy. Moreover, CTC clusters are suggested to add prognostic information to CTC enumeration alone but their significance is unknown in patients with newly diagnosed MBC. We aimed to evaluate whether longitudinal enumeration of circulating tumor cells (CTCs) and CTC clusters could improve prognostication and monitoring of patients with metastatic breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 32 publications
4
101
1
Order By: Relevance
“…This meta‐analysis, based on 21 studies, has shown that CTC count is an independent and quantitative prognostic factor in early breast cancer patients treated by neoadjuvant chemotherapy, and complements current prognostic models based on tumor characteristics and response to therapy . A very recent clinical prospective study that included 156 women with newly diagnosed metastatic breast cancer concluded that longitudinal evaluation of CTC and CTC clusters improves prognostication and monitoring in patients with metastatic breast cancer starting first‐line systemic therapy …”
Section: Circulating Tumor Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…This meta‐analysis, based on 21 studies, has shown that CTC count is an independent and quantitative prognostic factor in early breast cancer patients treated by neoadjuvant chemotherapy, and complements current prognostic models based on tumor characteristics and response to therapy . A very recent clinical prospective study that included 156 women with newly diagnosed metastatic breast cancer concluded that longitudinal evaluation of CTC and CTC clusters improves prognostication and monitoring in patients with metastatic breast cancer starting first‐line systemic therapy …”
Section: Circulating Tumor Cellsmentioning
confidence: 79%
“…39 A very recent clinical prospective study that included 156 women with newly diagnosed metastatic breast cancer concluded that longitudinal evaluation of CTC and CTC clusters improves prognostication and monitoring in patients with metastatic breast cancer starting first-line systemic therapy. 40 Detection of CTCs using the CellSearch system before neoadjuvant therapy was an independent prognostic factor of impaired clinical outcome, and when combined with pathologic complete response (pCR), it was shown to be helpful to stratify breast cancer patients for therapeutic interventions. 41 In 3173 patients with nonmetastatic (stage I-III) breast cancer, the presence of CTCs was found to be an independent predictor of poor disease-free, overall, breast cancerspecific, and distant disease-free survival.…”
Section: Breast Cancermentioning
confidence: 99%
“…This is slightly higher than recently reported by Vetter et al, who found 35% of their cohort had clusters present prior to treatment [26], using the Parsortix microfluidic device. Studies using the CellSearch™ system report cluster rates around 20% [27]. Current technologies significantly under-call the number of CTC clusters because few specialised devices exist for their detection.…”
Section: Discussionmentioning
confidence: 99%
“…The study was previously described in detail [27,28]. In brief, 168 women with newly diagnosed MBC, previously untreated for metastatic disease, were included in a prospective observational study at Skåne University Hospital and Halmstad County Hospital (ClinicalTrials.gov NCT01322893).…”
Section: Methodsmentioning
confidence: 99%